Exact traveling wave solutions of Chaffee–Infante equation in (2 + 1)‐dimensions and dimensionless Zakharov equation. (2nd September 2020) - Tahir, Muhammad; Kumar, Sunil; Rehman, Hamood; Ramzan, Muhammad; Hasan, Ahmad; Osman, Mohamed S.
Abstract : In this work, the generalized Kudryashov method is used to obtain the exact traveling wave solutions for two important nonlinear evolution equations, the Chaffee–Infante equation in (2 + 1)‐dimensions and the dimensionless Zakharov equation. The generalized Kudryashov method is successfully used for getting exact solutions of these nonlinear equations in the form of exponential function solutions and hyperbolic function solutions. Moreover, we have discussed the dynamical behaviors through graphical representation of the solutions obtained in this way.